Factors affecting the personal saving behaviour among UTAR staffs during covid-19 - Chia, Aii Lilien; Fang, Wei Yen; Low, Kai Chi; Poon, Tat Chi; Tan, Wei Li (2022)
This study is carried out to discover the factors affecting the personal saving behavior among UTAR staffs during Covid-19. The factors affecting the personal saving behavior among UTAR staffs during Covid-19 which included the independent variables of financial knowledge, financial self-efficacy, risk perception and income level. Social Cognitive Theory of self-regulation, Risk Perception Theory, Theory of Planned Behavior and Life Cycle Hypothesis will be used to explain the independent variables and dependent variables. The target respondents are academic staffs from UTAR Kampar campus who are between the ages of 21 and 70, with an aim to collect at least 217 of the questionnaire survey respondents. In this study, SPSS was used to help with data analysis. In the data analysis, the Reliability Test, Central Tendencies Measurement of Constructs, Pearson Correlation Analysis, and Multiple Regression Analysis are used. The findings revealed that independent variables such as financial knowledge, financial self-efficacy, and risk perception have a significant relationship with personal saving behavior among UTAR employees during Covid-19, with the exception of income level, which has an insignificant relationship with personal saving behavior among UTAR staffs during Covid-19. The independent variables can explain 0.556, or 55.6 percent of the variable in the dependent variable, according to R square. The research's limitations and recommendations are also included in this study for future researchers to gain a better nderstanding of UTAR staffs’ personal saving behavior during Covid-19.